Business Management in the Information Age: Use of Systems, Data Processing and Scalability for Organizational Efficiency - Martell, Karla; Cueto-Orbe, Rosa; Vela-del-Aguila, Santiago Luis; Torres-Manrique, Julio Iván; Reátegui-Villacorta, Karen; Alejandría-Castro, César Augusto (EAI Endorsed Transactions on Scalable Information Systems, 2024)
Abstract: This article reviews the challenges and opportunities facing companies in business management in the era of information. Challenges in managing large volumes of data, emerging trends in cybersecurity, and companies' ability to adapt to the digitalized environment are analyzed. The methodology used includes an exhaustive search of articles in indexed journals and the application of inclusion criteria to select 50 relevant articles. Key findings include obstacles in data management, the increasing sophistication of cyber threats, and business adaptation strategies such as digital transformation and the integration of emerging technologies. In conclusion, the importance of addressing these challenges and leveraging the opportunities presented by technology to enhance business efficiency and competitiveness is highlighted.
Keywords: Cybersecurity; Information Age; Scalability; Business Management; Digital Transformation